PENERAPAN MODEL TIPE PICTURE TO PICTURE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA - Prihanto, Subkhi (2013)
This study originated from problems arising from the lack of value of the learning outcomes of students with a percentage below 50% for hydrological science materials. The study was conducted by using the method of action research (PTK) with three cycles and for each cycle consisting of planning, implementation, observation and reflection. The experiment was conducted in SDN Buah Batu Lembang district, West Bandung regency. Subjects were students class V with the number of students 39 people consisting of 22 girls and 17 boys. Planning made like making the pictures clear, customized content for each cycle, as well as learning the instrument and learning the instrument as supporting research. Implementation of learning did well through pre activity, core activity (Exploration, Elaboration, Confirmation) and Post activity. In the implementation should use clear pictures, so students got better understanding from the material presented by the teacher. The results obtained by the first cycle class average 56.18 and the percentage of students passing grade 60.52%. Cycle II earned an average grade 66.21 and the percentage of students passing grade 62.16%. Cycle III obtained an average grade 69.72 and the percentage of students passing grade 83.78%. From the results of data per cycle showed an increase in student learning outcomes in science learning materials hydrological cycle using a model type picture to picture in SDN Buah Batu. Thus the application of the type of picture to picture models can be used in other learning tailored to the learning objectives to be achieved. Keywords: Picture to Picture Model, Student Learning Outcomes, Science Subjects on Hydrological Cycle Penelitian ini berawal dari permasalahan yang terjadi akibat dari kurangnya nilai hasil belajar siswa dengan presentase dibawah 50% untuk materi daur hidrologi. Penelitian dilakukan dengan menggunakan metode penelitian tindakan kelas (PTK) dengan tiga siklus dan untuk tiap siklusnya terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Penelitian dilaksanakan di SDN Buah Batu kecamatan Lembang, Kabupaten Bandung Barat. Subjek penelitian adalah siswa/i kelas V dengan jumlah siswa 39 orang yang terdiri dari 22 perempuan dan 17 laki-laki. Perencanaan yang dibuat seperti pembuatan gambar atau pemilihan gambar yang jelas, materi yang disesuaikan untuk tiap siklusnya, serta instrumen pembelajaran dan instrumen penelitian sebagai penunjang pembelajaran. Pelaksanaan pembelajarannya dilalui dengan baik mulai dari kegiatan awal, kegiatan inti (eksplorasi, elaborasi, konfirmasi) dan kegiatan penutup. Dalam pelaksanaannya harus menggunakan gambar yang jelas, sehingga siswa lebih memahami materi yang disampaikan guru. Hasil penelitian siklus I diperoleh rata-rata kelas 56,18 dan presentase ketuntasan belajar siswa yakni 60,52%. Siklus II diperoleh rata-rata kelas 66,21 dan presentase ketuntasan belajar siswa yakni 62,16%. Siklus III diperoleh rata-rata kelas 69,72 dan presentase ketuntasan belajar siswa yakni 83,78%. Dari hasil data tiap siklus menunjukkan adanya peningkatan pada hasil belajar siswa pada pembelajaran IPA materi daur hidrologi menggunakan model tipe picture to picture di SDN Buah Batu. Dengan demikian penerapan model tipe picture to picture disarankan untuk digunakan pada pembelajaran lainnya disesuaikan dengan tujuan pembelajaran yang ingin dicapai. Kata Kunci: Model tipe Picture to Picture, Hasil Belajar Siswa, Mata Pelajaran IPA mengenai Daur Hidrologi